The Association Between Total Protein Intake and All-Cause Mortality in Middle Aged and Older Korean Adults With Chronic Kidney Disease - Kwon, Yu-Jin; Lee, Hye Sun; Park, Go Eun; Kim, Hyung-Mi; Lee, Jung Joo; Kim, Woo Jeong; Lee, Ji-Won (Frontiers in Nutrition, 2022)
Background and aims: Over the past decades, the optimum protein intake for patients with chronic kidney disease (CKD) has been an important, controversial issue. Dietary protein restriction has been commonly recommended for patients with CKD for preserving kidney function. However, evidence of the associations between long-term protein intake and mortality is not consistent in patients with CKD. Therefore, we aimed to examine the associations between total protein intake and all-cause mortality in Korean adults with CKD. Methods: From three sub-cohorts of the Korean Genome and Epidemiology Study (KoGES) starting from 2001, total 3,892 participants with eGFR <60 mL/min/1.73 m2 (CKD stage 3-5) were included in this study. Dietary data were collected using food-frequency questionnaires at baseline. Deaths were followed from 2001 to 2019. Cox proportional hazards regression model was used to evaluate the association between protein intake and all-cause mortality. Results: During a median follow-up (min-max) of 11.1 years (0.3–15.1), 602 deaths due to all causes of mortality were documented. After adjustment for covariates, higher total protein intake was not associated with all-cause mortality [highest versus lowest quintile of total protein intake (g/kg/day) and proportion (%) (Q5 versus Q1), HR= 1.14 (0.75–1.72), and HR=0.87 (0.67–1.13)] in CKD stage 3-5 patients. Conclusion: Dietary protein intake was not associated with mortality from all causes in patients with CKD. Further research is needed to establish optimal protein intake levels and examine the impact of the dietary source of protein on various health outcomes and mortality in CKD.